The Possible existence of the millennium television advertisements - Benemerito, Annabelle Monje 1979-
This thesis is a quantitative study that is based on a grounded theory. It employed three research methods namely the Focus Group Discussion, the Focus Interview and the Textual Analysis. The respondents for the Focus Group Discussion were students from UP Integrated School and college students from UP Diliman. They were asked about their perception of the concept THE MILLENNIUM and if the concept is evident in television advertisements. Those that were interviewed for the Focus Interview were those classified as the Creator. They are the creative directors and copywriters of various advertising agencies. Likewise they were asked about their concept of THE MILLENNIUM and if this concept is reflected in television ads that were validated by the Textual analysis. From the study, it was incurred that the youth audience and the Creators have a common perception of THE MILLENNIUM. However, it appeared that they do not share the same opinion about the existence of the concept in television ads. It was concluded that the reason why they have a different opinions about the existence of THE MILLENNIUM concepts in ads is because the Creators are bound by certain objectives in the course of creating the ads. The youth on the other hand are so much exposed to the medium of television and messages about the concept from their immediate environment that they tend to associate images and messages to the event itself. Thus, they create a certain feel, an atmosphere or mindset directed towards the millennium.